Afektywna rzeźba zniszczenia Marii Bor - Tomczak, Karolina (Artium Quaestiones, 2025)
In the text Maria Bor’s Affective Sculpture of Destruction an attempt was made to present the issue of destruction in selected works of this artist as an expression of her affect and affective remembrance of war destruction, mainly universalized to the experiences of the general public. The artistic expression of affectivity in the material spatial medium and the author’s stylistics of existential figuration – residual and organic – was analysed. In addition to the affective perspective of art history, a detailed formal and partly contextual analysis was used, to finally prove the stylistic individualization of the affective sculpture expressing entropy and the strengthening of the creator’s subjectivity through its construction.